Efeito da intrusão de gado sobre a comunidade de formigas de serrapilheira em remanescentes florestais na Amazônia Meridional - Vicente, Ricardo Eduardo (2011)
Deforestartion driven by the expansion of cattle ranching activities towards the north of Mato Grosso transforms the landscape and is a threat to biological diversity. The issue associated to this kind of fragmentation is cattle intrusion in Areas of Permanent Preservation (APP) and the Legal Reserve (RL's). The impact due by cattle intrusion inside forest patches changes the structure of vegetation by grazing the understory and seedling, moreover, trampling caused by these large domestic herbivores compacts the soil. These structural changes caused by cattle operate synergistically with fragmentation. To assess cattle intrusion influence in forest remnants on the number of species and community composition of ants in leaf litter, were collected with Winkler extractor and manual collection for 15 minutes in 24 forest remnants in the municipality of Alta Floresta, MT, which ranged from 2.4 to 14480.5 ha. Of these, seven have a history of cattle intrusion. In order to verify if the impact of livestock would provide a greater flux of species between fragment and matrix, were collected at sampling points in the matrix adjacent to 50 meters from the edge of each remnant. Only manual collecting were made in matrix because there was no litter in these sites. In total there were 3,166 recorded occurrences of ants, belonging to 272 species, 57 genera and 11 subfamilies. These results shows that cattle intrusion changes the composition of litter ants, however, that this change is not related to the number of species per forest fragment since, despite expectations that are similar between areas with and without cattle. Although, the impact due by livestock in the forest areas does not make them more similar to the pasture matrix. This result is surprising and indicates that there is a substitution in the most susceptible ant species, typical of forested areas or by tolerant species of disturbed environments, probably typical of forest edges, but not invasive species from the matrix of pasture. Based on these results with changes caused by the cattle intrusion in forest remnants undertakes its role in biodiversity conservation of the landscape, changes in the Brazilian Forest Code that address preventive and mitigating measures should be taken. Future studies should help understanding the effect of the impact of different intensities and its territorial extension, which is very important to better understand the integrity of areas aimed to biodiversity conserving, often surrounded by a matrix of pastures.